The collagen cross‐linking enzyme lysyl oxidase is associated with the healing of human atherosclerotic lesions. (24th March 2014) - Ovchinnikova, O. A.; Folkersen, L.; Persson, J.; Lindeman, J. H. N.; Ueland, T.; Aukrust, P.; Gavrisheva, N.; Shlyakhto, E.; Paulsson‐Berne, G.; Hedin, U.; Olofsson, P. S.; Hansson, G. K.
Abstract: Background: Acute clinical complications of atherosclerosis such as myocardial infarction (MI) and ischaemic stroke are usually caused by thrombus formation on the ruptured plaque surface. Collagen, the main structural protein of the fibrous cap, provides mechanical strength to the atherosclerotic plaque. The integrity of the fibrous cap depends on collagen fibre cross‐linking, a process controlled by the enzyme lysyl oxidase (LOX). Methods and results: We studied atherosclerotic plaques from human carotid endarterectomies. LOX was strongly expressed in atherosclerotic lesions and detected in the regions with ongoing fibrogenesis. Higher LOX levels were associated with a more stable phenotype of the plaque. In the studied population, LOX mRNA levels in carotid plaques predicted the risk for future MI. Within the lesion, LOX mRNA levels correlated positively with levels of osteoprotegerin (OPG) and negatively with markers of immune activation. The amount of LOX‐mediated collagen cross‐links in plaques correlated positively also with serum levels of OPG. Conclusions: Lysyl oxidase may contribute to the healing of atherosclerotic lesions and to the prevention of its lethal complications. Mediators of inflammation may control LOX expression in plaques and hence plaque stability.